Crown root fracture imaging on Cone Beam Computed Tomography - Anak Agung Gde Dananjaya Agung; Ni Ketut Ayu Lestarini (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2021)
Objectives: This case report is aimed to describe the features of CBCT in assessing tooth fracture. Case Report: A 50-year-old man came with complaints of discomfort in the right lower jaw area, especially when used for chewing. The results of the percussion test were positive. CBCT examination showed that there was a radiolucent image of the enamel in the middle of the crown root to the 1/3 apical of the mesial and distal roots of tooth 47 which resembled a fracture line. The fracture line also appears to have reached the pulp. In addition, there is a well-defined radiolucent appearance with an irregular shape along the root from the buccal to lingual alveolar crest and accompanied by a decrease in the alveolar crest. The fracture that occurred in this case was from the enamel to the apical and involved the pulp, thus the radiodiagnosis on tooth 47 was a complicated crown root fracture with lateral periodontal cyst. Conclusion: CBCT can be used to help identify tooth fractures by obtaining a more accurate and useful value in differentiating conditions associated with fractures. CBCT provides data on the size and length of the fracture line and the size of the lesion.